Prevalence of hypocalcaemia and maternal complications among antenatal clinic attendees at the university of Port Harcourt teaching hospital - Eli, S; Enyindah, CE; Orluwene, CG; Ikimalo, J; Abam, DS (Nigerian journal of medicine, 2017)
BACKGROUND: Plasma Calcium level is not a routine laboratory test conducted during pregnancy. The role of calcium supplementation to prevent maternal complications of pregnancy such as pre-eclampsia and pregnancy induced leg cramps is conflicting. OBJECTIVE: To determine the prevalence of hypocalcaemia and maternal complications among antenatal clinic attendees. METHOD: Ten milliliters of blood sample were taken from each of the 90 pregnant women that met the inclusion criteria for the study. The plasma isolated from each woman was analyzed for calcium and albumin using calciumalbumin kit (lab 7225 spectrophotometer set Bran Scientific and Instrument Company, England).The data was analyzed using SPSS version 16. RESULTS: The prevalence of hypocalcaemia was 25.6% at recruitment and 40% in the third trimester. Sixty-five percent of the subjects who had hypocalcaemia in third trimester developed pre-eclampsia. In the hypocalcaemic group,the frequency of leg cramps was 23.3% and 27.8% at recruitment and at the third trimester respectively. Eight out of the 23(34%) subjects had pre-eclampsia in the normotensive group. CONCLUSION: The study revealed that high prevalence of hypocalcaemia was associated with advanced gestational age. In addition, there was a relationship between hypocalcemia, pre-eclampsia and pregnancy induced leg cramps. Thus calcium supplementation is recommended for those at risk of hypocalcaemia.